High Molecular and Cytogenetic Risk in Myelofibrosis Does Not Benefit From Higher Intensity Conditioning Before Hematopoietic Cell Transplantation: An International Collaborative Analysis. Issue 10 (30th October 2022) - Gagelmann, Nico; Salit, Rachel B.; Schroeder, Thomas; Badbaran, Anita; Rautenberg, Christina; Panagiota, Victoria; Wolschke, Christine; Thol, Felicitas; Cassinat, Bruno; Robin, Marie; Heuser, Michael; Reinhardt, Hans Christian; et al.
Abstract : There is no direct evidence to recommend specific conditioning intensities in myelofibrosis undergoing allogeneic hematopoietic cell transplantation, especially in the molecular era. We aimed to compare outcomes of reduced intensity (RIC) or myeloablative conditioning (MAC) transplantation in myelofibrosis with molecular information. The study included 645 genetically annotated patients (with at least driver mutation status available), of whom 414 received RIC and 231 patients received MAC. The median follow-up time from transplantation was 6.0 years for RIC and 9.4 years for MAC. The 6-year overall survival rates for RIC and MAC were 63% (95% confidence interval [CI], 58%-68%) and 59% (95% CI, 52%-66%; P = 0.34) and progression-free survival was 52% (95% CI, 47%-57%) and 52% (95% CI, 45%-59%; P = 0.64). The 2-year cumulative incidence of nonrelapse mortality was 26% (95% CI, 21%-31%) for RIC and 29% (95% CI, 23%-34%) for MAC ( P = 0.51). In terms of progression/relapse, the 2-year cumulative incidence was 10% (95% CI, 5%-19%) for RIC and 9% (95% CI, 4%-14%) for MAC ( P = 0.46). Higher intensity conditioning did not seem to improve outcomes for higher-risk disease, according to mutational, cytogenetic, and clinical profile. In contrast, patients with reduced performance status, matched unrelated donors, and ASXL1 mutations appeared to benefit from RIC in terms of overall survival.